THE IMPLEMENTATION OF TECHNO-PEDAGOGY TEACHING APPROACH FOR INDONESIAN SECONDARY SCHOOL TEACHERS IN JAVANESE GAMELAN LEARNING - Wibowo, Dhany Yufisa; Masunah, Juju; Milyartini, Rita; Karyono, Tri (International Journal of Education, 2025)
Since its recognition as a World Intangible Cultural Heritage by UNESCO, it is pivotal to preserve Gamelan musical instruments by introducing them to the younger generation; one of which is through teaching such Indonesian traditional musical instruments at schools. However, in practice, Javanese Gamelan learning in schools is often neglected, among other things, due to the lack of teacher knowledge, limited facilities, and lack of support from the school. The purpose of this research is to explore the concept of techno-pedagogy as an alternative teaching approach that can be developed and applied by teachers in Javanese traditional Gamelan music classrooms at secondary schools in Indonesia; utilizing technology and information media to ease students’ learning. This qualitative research was carried out by collecting data from interviews, document analysis, and review of previous literature related to the current purpose. Three participants (two experienced music teachers and one lecturer) were involved. The data obtained were then analyzed using qualitative coding techniques. The findings of this study demonstrate that the concept of techno-pedagogy provides teachers with the necessary abilities and resources to deliver Gamelan teaching in a more effective way and in accordance with the needs of today's students. By combining modern technology with a pedagogical approach, teachers can make the learning experience more engaging and accessible and allow students to explore Gamelan through interactive platforms such as M-Learning The results imply that teachers should adapt their teaching strategies to different learning situations to engage students effectively; particularly through the techno-pedagogy approach.